The Assessment of English Teachers’ Ability to Write A Scientific Article in English - Ardi Marwan (Lingua Cultura, 2017)
This article presented results of a study investigating several English teachers’ ability to write a scientific article. This was a qualitative research seeking to assess the scientific articles written by many English teachers. 25 English teachers who were currently pursuing the masters of education study at a university in Kalimantan were invited to become the research participants. The data were collected through the analysis of teachers’ articles and interviews with some of the teachers. The results reveal majority of the English teachers experienced difficulties producing articles ready to be published in good scholarly journals. Lack of scientific article writing experiences or practices and teachers’ English writing competence have been the major contributors of their inability to write good articles. This study, therefore, recommends the provision of relevant professional developments for English teachers to further improve their scientific article writing competence.